THE FRENCH POLICY TOWARDS ETHNIC MINORITIES IN THE CENTRAL HIGHLANDS - Nguyễn Văn Bắc (Tạp chí Khoa học Đại học Đà Lạt)
After bloodily suppressing the Cần Vương movement in the late nineteenth century, the French started conducting surveys of all geographic areas throughout the territory of Vietnam to provide bases for developing appropriate policies for each locality. The Central Highlands held special attraction, not only to colonial rulers, but also to scholars of various academic areas because of its important strategic location, abundant resources, and ethnic diversity. While substantial attention has been given to the history of the Central Highlands during the colonial period (for example, the group of works on the history of the Provincial Communist Party Committee and unification records of each province), limited attention has been bestowed upon the process of setting up the governmental system, arranging provincial administrative units, and the French policies for ethnic minorities. By examining legal documents issued by the Governor - General of Indochina and the Chief of State Bảo Đại, and by reviewing related studies, the author hopes to contribute some new insights about the points mentioned above.